Literature Review: The Relationship Between Discharge Planning and Post-Hospitalization Patient Control Compliance - SUSI HANDAYANI; Rahmawati, Fitria Dwi; Ndeso, Yasinta Safera; Umayanti, Resti; Choiriyah, Zumrotul (Proceedings of Conference on Health Universitas Ngudi Waluyo, 2026)
Discharge planning is an important component of nursing care aimed at ensuring continuity of patient care after hospital discharge. One of the success indicators of discharge planning is patient adherence to follow-up visits after hospitalization. This study aims to analyze the relationship between discharge planning and patient adherence to follow-up visits after hospital discharge based on a literature review. The method used is a literature review of five scientific articles published between 2022–2025. The articles were selected based on inclusion criteria consisting of cross-sectional, quasi-experimental, and descriptive studies discussing discharge planning and patient adherence to follow-up care. Data analysis was conducted descriptively by synthesizing the results of each article. The results showed that discharge planning is associated with and has an influence on patient adherence to follow-up visits after hospital discharge. The most influential factors include health education, the role of nurses, and education provided at discharge. The conclusion of this study is that optimal discharge planning can improve patient adherence to follow-up visits after hospital discharge. Therefore, strengthening the role of healthcare providers, especially nurses, in discharge planning is essential to improve healthcare quality and prevent rehospitalization.